Power Electronics Converters for Variable Speed Pump Storage - Othman Hassan Abdalla; Minxiao Han (International Journal of Power Electronics and Drive Systems (IJPEDS), 2013)
This paper proposed the power electronics solution to obtain variable speed of the variable-speed pump storage The study focused on the types of variable-speed pump storage consists of doubly fed asynchronous machine and power electronics converter. Power Electronics converters used in this model are cycloconverter, two levels, three levels voltage source- converter and H-bridge cascaded eleven levels converters. The total harmonic distortions of rotor currents of Doubly fed asychronous machine and speed change for each type of converters are analyzed. Study explained the H-bridge eleven level converter is the best solution than other types.All simulation models depended on the used of PSIM software program.DOI: http://dx.doi.org/10.11591/ijpeds.v3i1.1726